Mindfulness-Based Stress Reduction (MBSR) Group Intervention to Reduce Burnout among Caregivers in Nursing Home - Risky Adinda; Dini Rahma Bintari (Universitas Ahmad Dahlan, 2020)
Professional caregivers are prone to experience burnout. Burnout is a condition of physical, emotional, and mental fatigue caused by prolonged stress due to work negatively impacts work performance and well-being of professional caregivers. The present study aims to explore the effectiveness of group intervention using Mindfulness-Based Stress Reduction in reducing burnout and enhancing the psychological well-being of professional caregivers in a nursing home. Five caregivers (four males and one female) participated in four intervention sessions and a follow-up session. Maslach Burnout Inventory and Ryff’s Psychological Well-Being Scale was used to measure burnout and psychological well-being, respectively. Qualitative data were also obtained through interviews at the end of the intervention. Statistical analysis using the Wilcoxon Signed-Rank Test indicated that MBSR was not significantly effective in reducing burnout and enhancing psychological well-being. However, a trend of positive improvement was observed, indicating the potential benefits of MBSR for reducing burnout in professional caregivers. Limitations of this study are explained in the discussion section.